PERSEPSI DAN DILEMA PUSAT PELAYANAN KESEHATAN SEBAGAI KAWASAN BEBAS ROKOK - I Wayan Sudiadnyana (Poltekkes Kemenkes Denpasar, 2018)
ABSTRACT. Cigarette consumption problems and health impact of ever greater world, and so do in Indonesia. Policy Health Minister of Republic Indonesia call upon puskesmas to specified as free smoking area, not yet getting many attention of health care management. Puskesmas Kediri I Tabanan still now not yet been spicified as free smoking area, so that employees and visitor also there still smoking in puskesmas area. The objective of study was evaluated the readness of health officer to realize puskesmas as free smoking area. Research method was qualitative design with Rapid Asessment Procedure (RAP). Information as responder taken away from puskesmas health officer and visitor. Data collection with in-dept interviews, observation and documentation studies. Final data analysis using theme analysis. Results of study was showed perception of health officer to danger smoke to health no doubt again. Puskesmas health officer was agrred if puskesmas specified to free smoking area, and if this matter realized its estimeted no resistence either health officer and also visitor. Conclusion of this study was health officer basicaly have ready for realizing puskesmas as free smoking area. Suggested to management of puskesmas, so that immediately realize Puskesmas Kediri I as free smoking area.Keywords : Free smoking area, perception